2013
DOI: 10.1177/0261927x13499331
|View full text |Cite
|
Sign up to set email alerts
|

Latent Semantic Similarity and Language Style Matching in Initial Dyadic Interactions

Abstract: In the present study, we examined two indices of semantic similarity (i.e., latent semantic similarity [LSS], language style matching [LSM]) to determine their respective roles in initial, unstructured dyadic interactions. Transcripts of the dyad members’ conversations were used to compute the LSS and LSM indices, which were then correlated with various dyad-level behaviors and perceptions. The results suggest that LSS develops out of a highly involving interaction between mutually attentive and acknowledging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 19 publications
(27 reference statements)
6
63
1
1
Order By: Relevance
“…Most dyads clustered around .60, and 42.2% of the cases were below this level. Neither Babcock, Ta, and Ickes (2014) nor Ireland (Ireland & Pennebaker, 2010;Ireland et al, 2011) reported descriptives for LSM, so we do not know whether our data are (in)consistent with other reports.…”
Section: The Role Of Relationship Statuscontrasting
confidence: 83%
“…Most dyads clustered around .60, and 42.2% of the cases were below this level. Neither Babcock, Ta, and Ickes (2014) nor Ireland (Ireland & Pennebaker, 2010;Ireland et al, 2011) reported descriptives for LSM, so we do not know whether our data are (in)consistent with other reports.…”
Section: The Role Of Relationship Statuscontrasting
confidence: 83%
“…Like behavioral mimicry, linguistic mimicry is ubiquitous and serves as a strategic "social glue" (we like those we mimic, and mimic those we like; ) that can have positive or negative consequences across a range of human interactions (Babcock et al 2014;Lord et al 2015;Kulesza, Dolinski, Huisman and Majewski 2013;Ludwig et al 2013;O'Donnell et al 2015;Rains 2015;Richardson et al 2014;Yilmaz 2015). For example, higher levels of linguistic mimicry increase romantic interest between individuals who are speed-dating (Ireland et al 2011), increase preferences for products (Tanner et al 2008), and increase team performance, trust, and cohesion (Gonzales et.…”
Section: Behavioral and Linguistic Mimicrymentioning
confidence: 99%
“…There are a wide range of explanations for this type of repetition, which is also called priming. Researchers have claimed that priming serves as evidence that there is an abstract syntactic representation for production (Bock, ); that speakers are biased towards highly available representations (Bock & Loebell, ); that speakers and listeners attempt to align linguistic representations in order to facilitate communication (Pickering & Garrod, , ); that speakers are implicitly learning statistical regularities in their language and are attempting to match those statistics (Chang et al., ; Fine & Jaeger, ; Jaeger & Snider, ); and that speakers use the same linguistic structures as their listeners to signal social compatibility (Babcock, Ta, & Ickes, ; Ireland et al., ). Some of the above theories argue that producing a structure and hearing a structure should result in similar levels of priming because comprehension and production share syntactic representations (Pickering & Garrod, ; Tooley & Bock, ).…”
Section: Introductionmentioning
confidence: 99%